A Christian Synthesis of Aristotle's Character Friendship - Hahn, Michael (Studies in Christian ethics, 2025)
Friendship is a virtue that holds significant potential as a method of Christian virtue formation. The article begins with Aristotle's concept of character friendship found in the Nicomachean Ethics as an integral part of his overall account of moral goodness. The Aristotelian account serves as a valuable foundation as there are many elements that can be adopted in a Christian approach. Next the article engages the uniquely Christian understanding of friendship and how it transforms Aristotle's understanding beginning with the example of Jesus in the Gospels. Reflections on friendship in Augustine, Thomas Aquinas, and John Henry Newman are highlighted to respond to the criticism that Christian thinkers denigrated friendship between the early fifth and mid-nineteenth century. Finally, the article shows how Christian ethics might reach a critical synthesis of Aristotelian and Christian insights on friendship in order to propose friendship as a valuable method of Christian virtue formation.